Virtual Heritage A Guide - Champion, Erik (Ubiquity Press, 2021)
Virtual heritage has been explained as virtual reality applied to cultural heritage, but this definition only scratches the surface of the fascinating applications, tools and challenges of this fast-changing interdisciplinary field. This book provides an accessible but concise edited coverage of the main topics, tools and issues in virtual heritage. Leading international scholars have provided chapters to explain current issues in accuracy and precision; challenges in adopting advanced animation techniques; shows how archaeological learning can be developed in Minecraft; they propose mixed reality is conceptual rather than just technical; they explore how useful Linked Open Data can be for art history; explain how accessible photogrammetry can be but also ethical and practical issues for applying at scale; provide insight into how to provide interaction in museums involving the wider public; and describe issues in evaluating virtual heritage projects not often addressed even in scholarly papers. The book will be of particular interest to students and scholars in museum studies, digital archaeology, heritage studies, architectural history and modelling, virtual environments.